Cytotoxic and apoptosis-inducing effects of novel 8-amido isocoumarin derivatives against breast cancer cells - Das, Vishal; Kaishap, Partha Pratim; Duarah, Gauri; Chikkaputtaiah, Channakeshavaiah; Deka Boruah, Hari Prasanna; Pal, Mintu (Naunyn-Schmiedeberg's archives of pharmacology, 2021)
Isocoumarin is a lactone, a type of natural organic compound that is used as synthetic intermediates of several natural products and pharmaceutical compounds explored for their potential therapeutic applications like antifungal, antimicrobial, anti-inflammatory, and anticancer activities. In our previous work, we were the first group to report the use of amide C-N bond of isatins as the oxidizing directing group for the synthesis of 8-amido isocoumarin derivatives. Whereas in our present work, we have screened the cytotoxic effects of novel 8-amido isocoumarin derivatives (S1–S10) in human breast cancer MCF-7 and MDA-MB-231 cells. Our novel results revealed that N-(3-(4-methoxyphenyl)-1-oxo-4-(4-propylphenyl)-1H-isochromen-8yl)acetamide (S1) and N-(4-(3,5-difluorophenyl)-1-oxo-3-(p-tolyl)-1H-isochromen-8-yl) acetamide (S2) are the two potent compounds among the rest synthesized isocoumarin derivatives that are cytotoxic against MCF-7 and MDA-MB-231 cells, whereas less toxic to the non-tumorigenic IOSE-364 cells. Flow cytometry studies have confirmed the induction of apoptotic effects of compounds by Annexin V/PI double staining. We also observed the cytotoxic effects of S1 and S2, as evaluated by DAPI-PI immunostaining and H&E staining. The morphological alterations consistent with apoptotic blebs were observed in both cancer cells treated with compounds assessed by scanning electron microscopy. Overall, this present study strongly demonstrates that 8-amido isocoumarin derivatives have potent cytotoxic and apoptotic effects in breast cancer cells.